The Effect of Using Bromelain and Papain Enzymes on the Quality of Pure Fish Oil from Milkfish Silage (Chanos chanos) - Yosie Prayudha Arisky; Supriyanto Supriyanto; Mohammad Fakhry (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight Research • Milkfish silage  oil fatty acid profile • The quality of pure fish oil from milkfish silage (Chanos chanos) • The effect of using bromelain and papain enzymes